Corporate Social Responsibility - a Challenging Issue: Exploring the Challenges of Corporate Social Responsibility (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Corporate Social Responsibility is a way to manage thebusiness Undoubtedly “profitability”has always been the driving force and an undercurrent behind all thisdevelopment; but as every coin has two facets; growing cut throat competitionand business rivalries started taking heavy toll on the quality, transparency,environment and the society in general endangering the peaceful coexistence ofbusiness and society. The businesses houses started realizing that they wouldhave to rise over and above the profitability and take care of all thoseassociated with their survival in the society directly or indirectly. Thisrealization resulted into the concept of Corporate Social Responsibility (CSR). This research paper moves arounddeveloping an understanding about the corporate social responsibility (CSR). Insimple words, CSR can be defined as achieving commercial success in ways thathonor ethical value and respect people, communities and naturalenvironment.  Over the last two decadesethical consumerism can be linked to emergence of CSR Corporations preservegrowth through globalization. Companies use CSR methodology as strategic tacticto gain public support for their presence in global market. Business unitsadopting CSR practices are benefitted in terms of increased sales and strongBrand positioning, increased ability to attract and motivate employees, decreasedoperating costs increased appeal to investors and financial analysts andoverall increased market share in the global economy. The challenging forbusiness is to apply fundamental principal to make CSR sharper, smarter &focused on what really matters by focusing on priorities and reportingperformances in an open & transparent way, and then only the goal ofcorporate social responsibility can be achieved. The research paper moves onaround developing an understanding about the corporate social responsibility asa challenging issue.